Heparin increasing podocyte‐specific gene expressions. Issue 4 (April 2014) - Yaoita, Eishin; Yoshida, Yutaka; Nameta, Masaaki; Zhang, Ying; Fujinaka, Hidehiko; Magdeldin, Sameh; Xu, Bo; Yamamoto, Tadashi
Abstract Aim Heparin, a highly sulfated glycosaminoglycan, has been shown to have a renoprotective effect on renal diseases, but its mechanisms remain to be elucidated. In this study, we examined the effect of heparin on podocytes by using primary cultured podocytes positive for podocyte‐specific markers including podocin and podocalyxin. Methods Podocytes were cultured from highly purified glomeruli isolated by the method with renal perfusion with magnetic beads and digestion of collagenase. Podocyte‐specific gene expressions and proteins were examined by real‐time polymerase chain reaction (PCR), Western blotting and immunofluorescence microscopy. Results Real‐time PCR showed that addition of heparin to the culture media significantly upregulated most of the podocyte‐specific genes in a dose‐dependent and time‐dependent manner. Western blotting showed a marked increase in protein levels of nephrin and podocin. Podocin localization at cell–cell contact sites became conspicuous in the presence of heparin. The effect of heparin was observed even in culture media deprived of bovine foetal serum. Heparan sulfate, less sulfated than heparin, and hyaluronan did not show such effects, but sulfated dextran did markedly. Conclusion Heparin acts on cultured podocytes to increase podocyte‐specific gene expressions. A high degree of sulfation is crucial for the effect of heparin.